2010
DOI: 10.1002/ejoc.201001408
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid Catalyzed Asymmetric Friedel–Crafts Alkylation of Indole with 3‐Hydroxyisoindolin‐1‐one: Enantio­selective Synthesis of 3‐Indolyl‐Substituted Isoindolin‐1‐ones

Abstract: Chiral phosphoric acids have been proven to be effective organocatalysts for the asymmetric Friedel-Crafts alkylation of indoles with 3-hydroxyisoindolin-1-ones. The corresponding products were obtained in excellent chemical yields (up to 99 %) with moderate to excellent enantioselectivities (up to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Several instances have been reported previously where the 3,3′-substitution on the chiral phosphoric acid catalyst has been shown to reverse the sense of enantioselection. 10,13 …”
mentioning
confidence: 99%
“…Several instances have been reported previously where the 3,3′-substitution on the chiral phosphoric acid catalyst has been shown to reverse the sense of enantioselection. 10,13 …”
mentioning
confidence: 99%
“…28 Gratifyingly, the enantiomeric excess could be enhanced to 92e99% in some cases by a single recrystallization of product. As described before, the BINOLphosphoric acid catalyst initiates the iminium formation and creates a chiral environment via close ion pairing between the iminium and the phosphate species.…”
Section: No-acetalsmentioning
confidence: 99%
“…[83] Zhou et al reported the first intermolecular alkylation of indole with 3-hydroxyisoindolin-1-one in the presence of chiral H 8 -BINOL phosphoric acid (Scheme 15). [84] Under optimized reaction conditions, the unprotected indole reacted with 3-hydroxyisoindol-1-one (R 1 = H) 61 in the presence of chiral H 8 -BINOL phosphoric acid 62 (5 mol %) to afford the 3-substituted isoindoline-1-one 63 in 99 % yield and 83 % ee. The enantiomeric excess of 63 could be increased up to 99 % after a single recrystallization from methanol.…”
Section: Addition Of Indole Nucleophiles To Cyclic Nacyliminium Ions mentioning
confidence: 99%